Pattern and problem of poultry consumption by the rural and urban families of Fulbaria Upazila - Hai, MA; Mahiuddin, M; Howlider, MAR; Yeasmin, T (Journal of the Bangladesh Agricultural University, 2010)
The pattern and problem of poultry consumption by the rural and urban families of Fulbaria upazilla were studied. Data were collected through interview schedule from 100 respondents (50 from rural area and 50 from urban area). Problem confrontation index (PCI) in urban area 27 to 143 against the possible range of 0 to 150 and in rural area 33 to 138 against the possible 0 to 150. Overall area PCI was 60 to 281 against the possible range of 0 to 300. Nonavailability of day old chicks, lack of optimum amount of feed, unbalanced diets and fluctuating prices of eggs and meat were the acute problems hampered the consumption of poultry. The average farm size in urban and rural areas was 167.84 and 233.94 decimal. Livestock population consisted of 80% poultry and 20% large animal. Poultry contributed 4% of the total income in the rural area and 3% in the urban area. Rural people have less knowledge on health and nutrition than that of urban people. Poultry consumption in both rural and urban area is certainly very low. A positive correlation of age with poultry consumption implies that per capita poultry consumption is higher for older people. Reverse case is expected to build a healthy society. From correlations it can be concluded that in urban area increased farm size, increased livestock population, increased income, better knowledge on health and nutrition and decreased family size should increase per capita poultry consumption. Correlations also indicate that decreased family size and better knowledge on health and nutrition could minimize problems of poultry consumption. In rural area correlations computed impress that increased literacy, increased farm size, increased livestock population, increased income and better knowledge on health and nutrition should increase per capita poultry consumption. Whereas, increased income could remove problems of poultry consumption. Keywords: Poultry; Consumption; Problem confrontation index; Pattern and problem DOI: 10.3329/jbau.v6i2.4827 J. Bangladesh Agril. Univ. 6(2): 307-313, 2008